CONCRETE MATERIAL RESISTANCE WITH NICKEL WASTE MATERIAL SUBSTITUTION TO INTRUSION OF MICROORGANISM - ASHAD (NIM 35003006), HANAFI
This dissertation studies various aspects of concrete resistance material to intrusion of microorganism of which nickel waste is a partially substitution of cement. Damages of structure's components which have direct contacted with the environment where microorganism grows and expands are mostly found in Indonesian traditional market buildings. Experiments to observe deterioration of the concrete material include physical and mechanical aspects. Porosity, permeability coefficient, shrinkage, compressive and tensile strengths, modulus of elasticity, poisson's ratio, and stress-strain relationship are parameters to identify degradation of materials in the physical and mechanical properties. Microstructure and chemical compounds of concrete are also investigated. Changes in chemical compounds such as in calcium hydroxide, calcium silicate hydrate and minor chemistry compounds such ettringite, calcite, and rankinite are taken into consideration for the properties of concrete material. Scanning Electron Microscopy (SEM) and X-Ray Diffraction (XRD) are used for the experiments to trace existence of microorganism, micro crack, pore, and chemical elements and their composition. Coconut water is media to grow and to expands the microorganism in various phase. There are initially lag phase (adaptation) and nonactive phase (death) the microorganism. Identification result show that the microorganism groups is dominant as aspergillus niger (fungus) and sacchromycodes ludwigi (yeast). Both types of the microorganism have growth characteristic which in form of colony of the body size is between 0.05 um until 0.5 um. Through process of metabolic, both type of microorganism the oxidize carbohydrate of media so that form alcohol as new substrat. The new substrat decomposed by microorganism through aerob respiration systems so that produce a number of energy and organic matters. Testing result of chromotography by High Performance Liquid Chromotography (HPLC) indicates that the organic matters is acetate acid (CH3COOH). This organic matter can react with calcium hydroxide (CH) and calcium silicate hydrate (CSH) in concrete and has deterioration effect to physical and mechanical concrete properties. The effect of intrusion of microorganism can be minimized by use of 16% nickel slag powder. This percentage is bigger than the percentage 14.59% for the CaOAl2O3-SiO2 ternary system. Physical properties for concrete without nickel slag powder include porosity, permeability coefficient, and weight loss are increased according to time of intrusion. The improvement trend follows equation of geometry function. For concrete of 16% nickel slag powder, the improvement of porosity and permeability coefficient are as indicated by equation of saturated growth rate function. The effect of intrusion of microorganism to mechanical concrete properties reduced compressive strength. Compressive strength reduction for concrete without nickel slag powder may also follow the geometry function, while the concrete of 16% nickel slag powder, compressive strength reduction is also indicated by saturated growth rate function. Direct impact of activity of metabolic microorganism reduces calcium hydroxide compound in concrete materials. Calcium silicate hydrate compound does not give permanent effect compared with calcium hydroxide compound. In general from test and analysis result show that the concrete materials resistance due to intrusion of microorganism is also influenced by water-cement ratio.